Mainstream Media Strategy Embracing Muslim Centennials - R. Kusumalestari, Ratri; Satriani, Arba’iyah; N. Permatasari, Andalusia; Nurhasanah, Ajeng; T. Rahmawati, Mediani (KnE Social Sciences, 2023)
The mainstream mass media has recorded its history in the journey of Indonesian journalism. The development and condition of the Covid-19 pandemic that utilizes digitalization technology have forced the mainstream mass media to transform to survive. The mainstream media is still read by Gen Z or centennials even though in the onslaught of social media and the shift of the age of information seekers or readers. Despite using social media and news aggregators as their first information sources, centennials still use mainstream media to clarify dubious facts they found on digital media. This study explores how the mainstream mass media survive and embrace the 100th generation as them. The researcher used an approach with case study methods and data collection techniques using observation, in-depth interviews, and document studies. The research subjects are editors of online mainstream media, namely suaramerdeka.com, krjogja.com, pikiran-rakyat.com, and Republika.co.id. This study discusses the strategic differences between the online mainstream media in the regions and the national media. Three interest findings are the highlight of this study. First, the routine media and approaches used to embrace the centennial generation as a potential audience. Second, the existence of content creators in the ranks of journalists is a new phenomenon that presents pros and cons. Third, the Republika.com approach as a media that serves Muslim audiences to Muslim centennials. Lastly, the use of journalistic language style that is familiar to centennials. Keywords: mainstream media, Muslim centennials, content creator, media routine